2019
DOI: 10.1111/jabr.12173
|View full text |Cite
|
Sign up to set email alerts
|

Learning to cope with everyday instances of social exclusion: A review of emotional and cognitive strategies for children and adolescents

Abstract: Over 20 years of research has shown that social exclusion is a pervasive and powerful form of social threat. Social exclusion causes a wide variety of negative outcomes including negative emotions and threats to fundamental human needs (i.e., self-esteem). Most importantly, experiencing exclusion during childhood or adolescence can provoke long-term negative effects such as depression and anxiety disorders.Despite the growing interest in this domain, only recent studies have started to examine possible coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 104 publications
1
5
0
Order By: Relevance
“…Researchers have suggested that both of these coping strategies might be more easily implemented or impulsively used than other strategies, although no prior research has explicitly investigated this (e.g. Timeo et al, 2019). The current study provides support for this suggestion, with excluded participants more quickly learning that retrieving positive autobiographical memories is associated with reward.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Researchers have suggested that both of these coping strategies might be more easily implemented or impulsively used than other strategies, although no prior research has explicitly investigated this (e.g. Timeo et al, 2019). The current study provides support for this suggestion, with excluded participants more quickly learning that retrieving positive autobiographical memories is associated with reward.…”
Section: Discussionsupporting
confidence: 56%
“…Recalling positive memories does lead to an improved mood (Gillihan, Kessler, & Farah, 2007) and is a common strategy to repair negative moods (Josephson, Singer, & Salovey, 1996;Rusting & DeHart, 2000). Effective strategies to bolster threatened needs after social exclusion include positive refocusing, a cognitive emotion regulation strategy that involves bringing one's attention to a positive distraction, and self-affirmation, recalling important values and positive characteristics of the self (Timeo, Riva, & Paladino, 2019). Self-affirmation in particular is linked with lower aggression after social exclusion (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years in Italy, as in many other countries in the Organization for Economic Co-operation and Development (OECD), an educational reform process has been taking place aimed at reducing social exclusion in the classroom [1], that is "the experience of being kept apart from others physically or emotionally" [2]. Specifically, social exclusion may regard both children exhibiting aggressive behaviours (creating a management problem in school settings and impairing learning processes [3,4]) and children withdrawing into themselves (who have consequent interpersonal difficulties with their classmates). Cross-sectional and longitudinal studies have confirmed a strong relation between peer rejection and overt or relational forms of aggressive behaviours in childhood and adolescence (for a meta-analysis, see [5]) as well as between peer rejection and withdrawn behaviour (for a commentary, see [6]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they more often reported that students at their school have difficulty getting along, were mean to one another, and picked on other students [ 90 ]. Additionally, experimental studies found that teenagers exposed to rejection and manipulation responded more aggressively than others who were included [ 91 , 92 ], and that negative perceptions of one’s own peer status promoted increased levels of aggression in response to negative feedback from a peer in a controlled laboratory situation [ 93 ]. In this light, it can be expected that negative perceptions of peer relationships, indicators of which could be the level of perceived rejection by peers or the level of being disliked by them, will promote active cyberbullying behaviour.…”
Section: Introductionmentioning
confidence: 99%